Properties of Mortar Containing Ceramic Waste Powder And Effective Micro-Organisms - Dhanesh Kumar, Abdul Rahman Mohd. Sam, Sajjad Ali Mangi, Ruhal Pervez Memon, Sanghar Bhutto & Abdul Waheed (International Journal of Advanced Science and Technology, 2020)
Emission of carbon dioxide during the production of cement has turned the attention of many researchers to find its solution. Ceramic tiles are being used throughout the world, which increases the problem of its disposal after their usage. In this project, an attempt is made to explore the potential of using ceramic waste powder (CWP) as a cement replacement material in mortar. In this research an effective microorganism (EM) was used as water replacement with CWP in the mortar to get comparative analysis for usage of both materials in mortar. Characterization of ceramic waste powder was done to find its mechanical and physical properties. Mortar cubes having size of 50x50x50 mm were cast containing CWP and EM to find its fresh and hardened properties. Casting was done in two stages, in first stage mortar was cast containing CWP with the replacement percentage of 10%, 20%, 30%, 40%, and 50%. In the second stage of casting, 10% water was replaced with EM in the mortar with CWP percentage of 0%, 10% and 20%. Results revealed that mortar containing 20% CWP has proven to be better than normal mortar. However, mortar containing EM with no CWP has shown less effect in mechanical properties of mortar. On the other hand, EM has shown positive results when mixed with less percentage of CWP in mortar. The overall results revealed that ceramic wastes powder can be used as cement replacement materials in mortar for construction application and EM can be used with less percentage of CWP in mortar.